Chinese women with 29–30 FMR1 CGG repeats have an earlier menopause. (3rd May 2020) - Tang, R.; Chen, R.; Luo, M.; Lin, S.; Yu, Q.
Abstract: Purpose: A strong, well-established non-linear relationship exists between fragile X mental retardation ( FMR1 ) premutation and menopausal age. The aim of this study is to evaluate whether this relationship continues into the normal CGG repeat range. Methods: FMR1 CGG repeats of 111 Chinese postmenopausal women from a prospective cohort and the relationship with age at menopause were analyzed. Associations of FMR1 genotypes with annually measured estradiol and follicle stimulating hormone (FSH) levels were also assessed. Results: One premutation and two intermediate carriers were identified, with a prevalence of 0.90% and 1.80%, respectively. The age at menopause differed with statistical significance ( p  = 0.007) between women carrying bi-allelic 29–30 repeats (49.66 ± 3.26 years) and those carrying a different number of repeats (51.26 ± 2.74 years). Age at menopause among subgroups (≤28, 29–30, and ≥31 repeats) of alleles 1 and 2 were also different ( p  = 0.014, p  = 0.044). FSH trajectories to final menstrual period differed between women with the bi-allelic 29–30 repeats and others ( p  = 0.019). Conclusions: Women with 29–30 FMR1 CGG repeats may experience menopause approximately 2 years earlier than those carrying ≤28 or ≥31 CGG repeats, and have a longer FSH fluctuant period.